Irving Brant papers - Brant, Irving, 1885-1976.
Correspondence, memoranda, speeches, writings, research notes, testimonies, newspaper clippings, and other papers reflecting Brant's newspaper career primarily as editor of the St. Louis Star (later the St. Louis Star-Times), his work with the Franklin D. Roosevelt presidential administration as speechwriter and conservation consultant for U.S. secretary of the interior Harold L. Ickes, and his literary career as a playwright. Subjects include civil rights and liberties, conservation, constitutional questions, and economic and foreign policy during the Roosevelt administration. Includes material pertaining to Brant's work as editorial writer for the Chicago Sun and to his historical studies of James Madison, the United States Constitution, and the U.S. Bill of Rights.
Includes Brant's testimony before congressional committees on conservation, constitutionality of anti-poll tax legislation, revision of Senate filibuster rules, and suffrage for the citizens of Washington, D.C., and Supreme Court reorganization. Documents his activities with the American Civil Liberties Union, National Audubon Society, Overseas Writers Club, and the Emergency Conservation Committee which led to the establishment of Olympic Peninsula, Olympic National Park, Washington (State).
Correspondents include James Abourezk, Dean Acheson, Clarke F. Ansley, Roger N. Baldwin, Charles A. Beard, Francis L. Berkeley, Francis Biddle, Hugo LaFayette Black, Bruce Bliven, William J. Brennan, James W. Brown, Edmond Cahn, Benjamin N. Cardozo, Emanuel Celler, David Laurance Chambers, Henry Steele Commager, Thomas G. Corcoran, James Couzens, Jay N. Darling, Irving Dilliard, Paul H. Douglas, William O. Douglas, Don Edwards, Marshall Field, Felix Frankfurter, John T. Frederick, Mark O. Hatfield, William T. Hornaday, Hubert H. Humphrey, Harold L. Ickes, Jacob K. Javits, Alice Kauser, James Jackson Kilpatrick, John P. Lewis, Edward C. Mabie, Dumas Malone, Ben Mellon, Walter F. Mondale, Priestly Morrison, Grace Morse, Wayne L. Morse, Allan Nevins, George W. Norris, John B. Oates, Drew Pearson, Marlen Edwin Pew, Ezra Pound, Elzey Roberts, Don W. Robinson, Franklin D. Roosevelt, Carl T. Rowan, Wiley Rutledge, Harrison E. Salisbury, Carl Sandburg, Arthur M. Schlesinger, Eric Sevareid, Willard Shelton, Frank Albert Smothers, Adlai E. Stevenson, Harlan Fiske Stone, Norman Lee Swartout, E.G. Swem, Frank W. Taylor, Charles H. Townes, Harry S. Truman, Oswald Garrison Villard, Henry A. Wallace, Earl Warren, James Russell Wiggins, Aubrey Willis Williams, C. Vann Woodward, and the Bobbs-Merrill Company.
Library of Congress Music Division.
Library of Congress Prints and Photographs Division.
Author, historian, and newspaper editor. Full name: Irving Newton Brant.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Abourezk, James G., -- 1931- -- Correspondence; Acheson, Dean, -- 1893-1971 -- Correspondence; Ansley, Clarke F. -- 1869-1939 -- Correspondence; Baldwin, Roger N. -- 1884-1981 -- Correspondence; Beard, Charles A. -- 1874-1948 -- Correspondence; Berkeley, Francis L. -- 1911-2003 -- Correspondence; Biddle, Francis, -- 1886-1968 -- Correspondence; Black, Hugo LaFayette, -- 1886-1971 -- Correspondence; Bliven, Bruce, -- 1889-1977 -- Correspondence; Brennan, William J. -- 1906-1997 -- Correspondence; Brown, James W. -- 1873-1959 -- Correspondence; Cahn, Edmond, -- 1906-1964 -- Correspondence; Cardozo, Benjamin N. -- 1870-1938 -- Correspondence; Celler, Emanuel, -- 1888-1981 -- Correspondence; Chambers, David Laurance, -- 1879-1963 -- Correspondence; Commager, Henry Steele, -- 1902-1998 -- Correspondence; Corcoran, Thomas G. -- Correspondence; Couzens, James, -- 1872-1936 -- Correspondence; Darling, Jay N. -- 1876-1962 -- Correspondence; Dilliard, Irving, -- 1904-2002 -- Correspondence; Douglas, Paul H. -- 1892-1976 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Edwards, Don, -- 1915- -- Correspondence; Field, Marshall, -- 1893-1956 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Frederick, John T. -- 1893-1975 -- Correspondence; Hatfield, Mark O., -- 1922-2011 -- Correspondence; Hornaday, William T. -- 1854-1937 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Ickes, Harold L. -- 1874-1952.; Ickes, Harold L. -- 1874-1952 -- Correspondence; Javits, Jacob K. -- 1904-1986 -- Correspondence; Kauser, Alice, -- 1872-1945 -- Correspondence; Kilpatrick, James Jackson, -- 1920-2010 -- Correspondence; Mabie, Edward C. -- 1892-1956 -- Correspondence; Madison, James, -- 1751-1836.; Malone, Dumas, -- 1892-1986 -- Correspondence; Mellon, Ben -- Correspondence; Mondale, Walter F., -- 1928- -- Correspondence; Morrison, Priestly, -- 1872-1938 -- Correspondence; Morse, Grace -- Correspondence; Morse, Wayne L. -- 1900-1974 -- Correspondence; Nevins, Allan, -- 1890-1971 -- Correspondence; Norris, George W. -- 1861-1944 -- Correspondence; Pearson, Drew, -- 1897-1969 -- Correspondence; Pew, Marlen Edwin, -- 1878-1936 -- Correspondence; Pound, Ezra, -- 1885-1972 -- Correspondence; Roberts, Elzey -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Rowan, Carl T. -- 1925-2000 -- Correspondence; Rutledge, Wiley, -- 1894-1949 -- Correspondence; Salisbury, Harrison E. -- 1908-1993 -- Correspondence; Sandburg, Carl, -- 1878-1967 -- Correspondence; Schlesinger, Arthur M. -- 1917-2007 -- Correspondence; Sevareid, Eric, -- 1912-1992 -- Correspondence; Shelton, Willard -- Correspondence; Smothers, Frank Albert, -- 1901- -- Correspondence; Stevenson, Adlai E. -- 1900-1965 -- Correspondence; Stone, Harlan Fiske, -- 1872-1946 -- Correspondence